Pemasaran Digital Bisnis Abon Ikan untuk Meningkatkan Jangkauan Pasar - Binti Nur Asiyah; Ahmad Budiman; Jusuf Bachtiar; Laini Khofifah; Adinda Putri Yesa Isnawati (Jurnal Al Basirah, 2026)
The background of this community service activity is the potential for abundant fish catch in Besole Village, Tulungagung Regency and the potential for human resources with expertise in processing tuna fish floss, which should be able to reach a wider market. In fact, the production of tuna fish floss by the female fishing community still relies on orders from the surrounding community. The community has not taken advantage of the opportunities for technological development for business purposes due to their lack of knowledge in developing existing businesses. The majority of them use social media which is a form of technological development as a medium for entertainment, information, and communication. This community service activity was carried out using the Asset Based Community Development (ABCD) method. The solution provided to the community to develop the market reach of tuna fish floss products is by using digital marketing through social media platforms such as WhatsApp, Facebook, and TikTok. The results of the community service activity are increasing the knowledge of the female fishing community regarding the use of digital technology through social media as a marketing medium that can be implemented in marketing activities. The community applies this knowledge to market its products, namely tuna fish floss, in reaching a wider market. The practical implication of this activity is so that the fishing community can be consistent in marketing by utilizing technological developments to support business development.